PENGARUH SUPERVISI AKADEMIK KEPALA MADRASAH TERHADAP KOMPETENSI PEDAGOGIK GURU MTS AL HIKMAH MAKARTI MULYA 2021/2022 - Binti Umi Istichomah; Achmad Sarbanun; Rina Setyaningsih (UNISAN JURNAL, 2022)
Educator competence is basically a description of what a person can do in a job, in the form of activities, behaviors and results that should be displayed or shown. In order to be able to do his job, of course a person must have the ability in the form of knowledge, attitudes and skills that are in accordance with his field of work and then actualized by educators in carrying out professional duties. Pedagogic competence is the ability to manage student learning which includes understanding students, designing and implementing learning, evaluating learning outcomes and developing students to actualize various competencies they have. Clinical supervision is part of academic supervision whose implementation is only focused on the teaching performance of educators (centered on educators) which includes aspects of educators' teaching abilities (planning, learning, and personal social). Based on the results of the research that the author did, it can be concluded that the results of the academic supervision of the head of Madrasah on the pedagogic competence of teachers, based on the findings: There is a significant effect between the academic supervision of the head of Madrasah and the pedagogic competence of teachers. This is indicated by the t arithmetic value of 3.734, and this value is greater and the t table at a significant level of 5% is 2.048 or (3.734 > 2.048). This means that the better the academic supervision of the Madrasah principal carried out by the Madrasah principal from the aspects of planning, implementation, and evaluation of learning, the better the pedagogical competence of teachers in learning. On the other hand, the less good the academic supervision of the Madrasah principal is carried out by the Madrasah principal, the lower and the less maximal the teacher's pedagogic competence in learning. Keywords: Academic Supervision of Madrasah Principals, Teacher's Pedagogic Competence